Dampak Perceraian di Bangkan Enrekang - Sri Devi (Rayhan Intermedia, 2019)
This research aims to find out: (1) How is the Divorce Process in the Bangkan Hamlet of Enrekang Regency. (2) What are the factors and causes of Divorce in the Bangkan Hamlet of Enrekang Regency. (3) What is the impact of Divorce in the Bangkan Hamlet of Enrekang Regency. In this study using the type of kulaitatif research written in descriptive. The technique of data collection is done by observation, interview and documentation. This study involved 12 informants. Based on the results of the research in the field, it shows that the divorce process in the District of Enrekang just happened and even some of the divorced people rarely filed their divorce cases with the Enrekang Religion Court for certain reasons, then the factors that caused the Divorce in the Bangkan Village in Enrekang District . These factors include, (a) internal factors (1) economic factors, (2) lack of responsibility, (3) disputes and domestic violence (domestic violence), (4) infidelity, (5) marriages without love and matchmaking parents. Whereas the impact is, (a) Phosphorous Impact: (1) Feelings of relief after divorce (b) Negative Impact (1) Children are only close to one of their parents.